Contract management : better practice guide - Australian National Audit Office (Canberra : Australian National Audit Office, 2001)
This Guide focuses on the application of risk management, which is an integral part of the contract management process, particularly the transition phase, ongoing management and succession planning associated with contracted goods or services. This Guide does not provide advice for all types of contracts and contract situations. In the complex and ever changing world of contracts, it is not practicable for one Guide to cover all the issues facing contract managers of very large and complex contracts, such as those for major construction or defence work. This Guide focuses specifically on the management of contracts as opposed to the management of projects.
"Better practice".
"February 2001".
Also available in an electronic version via the Internet. Address as of 25/10/01:http://www.anao.gov.au
The electronic version of the document is provided in text format as well as in pdf format. To download/view the pdf format you will need an Adobe Acrobat Reader on your PC.
Keywords: Contracting out -- Australia -- Management